THE POLITICAL SIGNIFICANCE OF THE "ONE PLACE ONE ROAD" INITIATIVE - Uzokov Jorabek To‘ychi O‘g‘li (Scholar Express Journals, 2022)
This article reveals the political aspects of the largest economic project of the People's Republic of China in the 21st century, "One Place One Road". Key words: "One space one road", "Chinese dream", geopolitics, world order, civilization, logistics, "Silk Road economic belt", "Sea route in the 21st century", colonization, expansion.
Keywords: One belt-one road; China dream; geopolitics; world order